Спільне використання міліметрових та субміліметрових хвиль - Лютий, А. О. (ХНУРЕ, 2024)
Current new 5G millimeter-wave (mm-wave) radio (NR) systems, as well as future 6G radio access technologies (RATs) in the terahertz (THz) band, will rely heavily on beamforming to combat excessive path loss. In addition, both RATs are designed for the same inelastic traffic that requires high data rates and is susceptible to blocking phenomena. To improve service reliability in these systems, multiple connections can be used to dynamically switch ongoing sessions between the two technologies. The purpose of this work is to investigate the use of millimeter and submillimeter waves for joint use.
Keywords: субміліметрові хвилі; міліметрові хвилі